Observation of the Identical Rigidity Dependence of He, C, and O Cosmic Rays at High Rigidities by the Alpha Magnetic Spectrometer on the International Space Station - Aguilar M; Cavasonza LA; Alpat B; Ambrosi G; Arruda L; Attig N; Aupetit S; Azzarello P; Bachlechner A; Barao F; Barrau A; Barrin L; et al. (AMER PHYSICAL SOC, 2022)
We report the observation of new properties of primary cosmic rays He, C, and O measured in the rigidity (momentum/charge) range 2 GV to 3 TV with 90 x 10(6) helium, 8.4 x 10(6) carbon, and 7.0 x 10(6) oxygen nuclei collected by the Alpha Magnetic Spectrometer ( AMS) during the first five years of operation. Above 60 GV, these three spectra have identical rigidity dependence. They all deviate from a single power law above 200 GV and harden in an identical way.